Muon $$g-2$$ g - 2 anomaly and $$μ $$ μ – $$τ $$ τ -philic Higgs doublet with a light CP-even component - Hong-Xin Wang (SpringerOpen, 2021)
Abstract We examine the possibilities of accommodating the muon $$g-2$$ g - 2 anomaly released by Fermilab in the 2HDM with a discrete $$Z_4$$ Z 4 symmetry in which an inert Higgs doublet field ( $$H,~A,~H^± $$ H , A , H ± ) has the lepton flavor violation $$μ $$ μ – $$τ $$ τ interactions. We assume the Yukawa matrices to be real and symmetrical and investigate the case of light H (5 GeV $$<m_H<$$ < m H < 115 GeV). After imposing relevant theoretical and experimental constraints, especially for the multi-lepton searches at the LHC, we find that the muon $$g-2$$ g - 2 anomaly can be explained within $$2σ $$ 2 σ confidence level in the region of 5 GeV $$<m_H<20$$ < m H < 20 GeV, 130 GeV $$< m_A~(m_{H^± })<$$ < m A ( m H ± ) < 610 GeV, and 0.005 $$<ρ<$$ < ρ < 0.014. Meanwhile, the $$χ ^2_τ $$ χ τ 2 fitting the data of lepton flavour universality in the $$τ $$ τ decays approaches to the SM prediction.